An Exploration of Self-Directed Learning in Speaking English - Nurdiana, Nurdiana; Roswati, Roswati; Afrizal, Afrizal; Gusmuliana, Paidi; Dermawan, Rezki (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study focused on exploring the methods of self-directed learning employed by the tenth grade of language class at Man 1 Pekanbaru students to enhance their speaking skills. A descriptive qualitative approach was utilized for this investigation. The study involved five students as participants. Meanwhile, as the object is self directed learning in speaking English. Data collection technique was were used interview; the researchers recorded the students’ answers; and documentation which used video or voice recordings individually, dialogue, conversation. The research findings showed that students used some media for independent learning, they are: listening to the music, watching the movie with English subtitle, playing games, learning from native on YouTube, learning any accents, reading an article and comic, E-learning, and following the community.